Compliance with standard precautions in inpatient healthcare settings in the Czech Republic: a cross-sectional survey - Pokorná, Andrea; Dolanová, Dana; Pospíšil, Michal; Búřilová, Petra; Mužík, Jan (Central European Journal of Public Health, 2020)
OBJECTIVE: The study evaluates compliance with declared hygienic standards carried out by healthcare professionals in clinical practice within their scope of direct patient care and the maintenance of medical tools and devices in healthcare facilities in the Czech Republic. METHODS: Cross-sectional questionnaire study focused on the standards of safe health care. All 80 addressed healthcare providers were also involved in the 2018 Adverse Event Reporting System (AERS) pilot project. Responses were scored on a 6-level scale, from "always" (100 points) to "never" (0 points). The evaluation was performed according to the frequency of responses and the average index (max. 100 points). Data analysis was performed using IBM SPSS Statistics version 22 (level of significance 1% and 5%). RESULTS: There were statistically processed 2,016 questionnaires (100%). Most respondents stated their job classification as non-medical healthcare professionals (NHP) working at a patient's bedside (73%), physicians (16%), or other NHP (11%). As per their medical specialty, 43% of the respondents practice internal medicine, 28% surgery, 14% psychiatry, 9% long-term inpatient care, and 6% stated other fields of medicine. The lowest declared compliance was registered in the statement "I use a face mask when exposure to air-transmitted pathogens is anticipated" (rating index 80 points). The highest compliance (99.4 points) was registered in the statement: "I discard used sharp materials into sharps containers." CONCLUSION: In the surveyed healthcare facilities within the Czech Republic, overall compliance with hygiene standards is at a good level. Declared differences in compliance with hygiene standards in the selected items of the questionnaire are influenced by multiple factors. Generally, a higher level of compliance is linked to increasing age, years of practice, and a higher level of education. When comparing professional groups, a higher level of compliance with hygiene standards was registered in the NHP group.
Keywords: Cross-Sectional Studies; Practice Guidelines as Topic; Guideline Adherence; Česká republika; Czech Republic; průřezové studie; průzkumy zdravotní péče; směrnice pro lékařskou praxi jako téma; Health Personnel; lidé; Humans; zdravotnický personál; Health Care Surveys; dodržování směrnic; zdravotnická zařízení; Health Facilities